O-008 Size and location of ruptured intracranial aneurysms in a consecutive series of 588 patients with first-time acute subarachnoid hemorrhage treated endovascularly at a tertiary referral medical center over a 16-year time period. (4th July 2012) - Almandoz, J Delgado; Fease, J; Crandall, B; Kadkhodayan, Y; Scholz, J; Anderson, R; Tubman, D
Abstract : Purpose: To assess the size and location of ruptured intracranial aneurysms in patients presenting with first-time acute subarachnoid hemorrhage (SAH) treated endovascularly at a tertiary referral medical center over a 16-year period. Methods: We retrospectively reviewed the size and location of ruptured intracranial aneurysms in all patients presenting to our institution with first-time acute SAH who underwent endovascular treatment from June 1, 1995 until January 31, 2012. The aneurysm location and maximum sac dimension were recorded utilizing catheter angiography. In patients with multiple aneurysms, we recorded data for the aneurysm thought most likely to be responsible for the SAH based on SAH distribution, maximum aneurysm sac dimension and sac morphology. Results: A total of 1681 intracranial aneurysms underwent endovascular treatment at our institution during the study's 16-year time period. Of these, 613 (36.5%) ruptured aneurysms were treated emergently in 588 patients with first-time acute SAH (393 females and 195 males, mean age 54.9 years, range 7–97 years). In 22 patients (3.7%), two or more intracranial aneurysms were treated emergently due to the inability to definitely identify the causative aneurysm. The most common ruptured aneurysm locations were anterior communicating (36.5%), posterior communicating (19.6%), middle cerebral (13.5%), internal carotid (11.4%) and basilar (7.8%) arteries (Abstract O-008 table 1 ). Overall mean ruptured aneurysm maximum sac dimension was 6.5 mm (range 1.3–30 mm, median 5.7 mm), 6.5 mm for anterior circulation aneurysms (range 1.7–30 mm, median 5.3 mm) and 6.4 mm for posterior circulation aneurysms including the posterior communicating artery (range 1.3–27 mm, median 6 mm). In our series, 373 (60.8%) of the ruptured intracranial aneurysms had a maximum sac dimension <7 mm and only 106 (17.3%) ruptured intracranial aneurysms had a maximum sac dimension ≥10 mm. Nearly half (48.5%) of the ruptured intracranial aneurysms treated endovascularly at our institution had a maximum sac dimension ≤5 mm. Conclusion: The majority (61%) of ruptured intracranial aneurysms treated endovascularly for first-time acute SAH at our institution had a maximum sac dimension <7 mm. These findings suggest that the data from the ISUIA trial which reported that the risk of SAH from intracranial aneurysms <7 mm in size is very low should be interpreted with caution. Competing interests: None.